Cultural modulation of the neural correlates of emotional pain perception : the role of other-focusedness - Cheon, Bobby Kyungbeom (2014)
Cultures vary in the extent to which they emphasize group members to habitually attend to the needs, perspectives, and internal experiences of others compared to the self. Here we examined the influence that collectivistic and individualistic cultural environments may play on the engagement of the neurobiological processes that underlie the perception and processing of emotional pain. Using cross-cultural fMRI, Korean and Caucasian-American participants passively viewed scenes of others in situations of emotional pain and distress. Regression analyses revealed that the value of other-focusedness was associated with heightened neural response within the affective pain matrix (i.e. anterior cingulate cortex and insula) to a greater extent for Korean relative to Caucasian-American participants. These findings suggest that mindsets promoting attunement to the subjective experience of others may be especially critical for pain-related and potentially empathic processing within collectivistic relative to individualistic cultural environments.